Biochemical pathways : an atlas of biochemistry and molecular biology - Schomburg, D. (Dietmar); Michal, Gerhard (Hoboken, N.J. : John Wiley & Sons, 2012)
'Covering a wide range of subject matter, including biochemistry, molecular and cell biology, medicine, chemistry, and allied health, Biochemical Pathways is a full-color, easy-to-use resource for students and professionals. This information-packed reference features a unique summary of biochemical pathways based on the well-known Biochemical Pathways chart. Included is descriptive information about properties such as enzymes, chemicals, proteins, and DNA, all of which act together to create an elaborate chain that drives all biological functions. Completely updated, this new edition continues to play a valuable role in this important scientific field'--
'Biochemical Pathways: An Atlas of Biochemistry and Molecular Biology, Second Edition, explains the multi-step chemical reactions (for example, carbohydrate metabolism pathways) that occur in biological systems (e.g., within cells and organelles). The chemical reactions, location within the cell, structure and function of proteins and nucleic acids (including the enzymes), small molecules (carbohydrates, amino acids, lipids, steroids, nucleotides) involved, vitamins and cofactors present, storage of information in DNA and translation into proteins, viruses infecting systems, various protein mechanisms, respiration processes, cellular communication and regulation, transport, defense, and blood coagulation are all discussed in detail'--
Introduction and general aspects / Gerhard Michal and Dietmar Schomburg -- The cell and its contents / Gerhard Michal and Dietmar Schomburg -- Metabolism -- Protein biosynthesis, modification and degradation -- Viruses / Klaus Klumpp -- Transport -- Signal transduction and cellular communication / Gerhard Niederfellner -- Immune system / Ernst Peter Rieber -- Blood coagulation and fibrinolysis / Peter M$1#7H(Bler -- Biochemical networks, bioinformatics and systems biology / Dietmar Schomburg .s
Machine generated contents note: Chapter 1. Introduction and general aspects, chemistry and physical chemistry Gerhard Michael and Dietmar Schomburg Chapter 2. The cell and its contents: Enzymes, nucleic acids, and polymeric carbohydrates and lipids Gerhard Michal and Dietmar Schomburg Chapter 3. General metabolism in animals, plants and bacteria 3.1 Carbohydrate Metabolism and Citrate Cycle 3.2 Amino Acids and Derivatives 3.3 Tetrapyrroles 3.4 Lipids amd Glycolipids 3.5 Steriods and Isopreniods 3.6 Nucleotides and Nucleosides 3.7 Cofactors and Vitamins 3.8 Nucleic Acid Metabolism in Bacteria 3.9 Nucleic Acid Metabolism in Eukarya 3.10 Special Bacterial Metabolism and Biosynthesis of Antimicrobials 3.11 Electron Transfer Reactions and Oxidative Phosphorylation 3.12 Photosynthesis 3.13 Plant Secondary Metabolism Chapter 4. Protein biosynthesis, modification and degradation 4.1 Protein Synthesis in Bacteria 4.2 Protein Biosynthesis in Eukarya 4.3 Cell Cycle in Eukarya 4.4 Posttranslational Modification of Proteins 4.5 Protein Folding, Transport / Targeting and Degradation Chapter 5. Viruses Klaus Klumpp Chapter 6. Transport systems 6.1 Transport Through Membranes 6.2 Transport of Lipids in Plasma 6.3 Oxygen Transport by Hemoglobin Chapter 7. Signal transduction and cellular communication Gerhard Niederfellner Chapter 8. Immune system 8.1 Components of the Immune System 8.2 Generation of a Specific Immune Response 8.3 Pathologic Immune responses 8.4 Adhesion of Leukocytes Chapter 9. Blood coagulation and fibrinolysis P. Mueller Chapter 10. Biochemical networks, bioinformatics and systems biology Dietmar Schomburg .
Includes bibliographical references and index.
Keywords: Metabolism -- Atlases